Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper examines the strengthening of the external current account for the Netherlands. It reviews this issue, concluding that the change in corporate profitability in a new wage environment was a crucial element, alongside fiscal consolidation, in turning around the current account-which has now moved into strong surplus. The paper analyzes the performance of the financial sector. It also reviews the experience of a decade and a half in a de facto monetary union for the Netherlands.